1992
DOI: 10.1103/physrevlett.68.2810
|View full text |Cite
|
Sign up to set email alerts
|

Hysteretic solidification of surfaceHe4measured by the modification of the specularity of

Abstract: We have measured the superfluid fraction of 3 He in pores of sintered silver. The superfluid fraction, which is suppressed by confinement, increases with pressure due to the decreasing coherence length. Coating the surfaces with a thin film of 4 He partially restores the suppressed superfluidity, but above 17 bars this effect diminishes as the 4 He film solidifies. This solidification occurs over a range of about 9 bars and is hysteretic. With a slightly thicker 4 He film, solidification occurs at pressures gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 20 publications
(53 reference statements)
1
15
0
Order By: Relevance
“…However, experiments with silica aerogels do not show a clear evidence of the magnetic channel. In particular, the observed A-like and B-like phases correspond to A and B phases of bulk 3 He, regardless of presence or absence of 4 He [8][9][10][11][12][13][14]. Moreover, the superfluid transition temperature of 3 He in aerogel (T ca ) is independent on the coverage at high pressures [8,12] but slightly higher in presence of the coverage at lower pressures [15,16] probably due to the change of the scattering specularity.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…However, experiments with silica aerogels do not show a clear evidence of the magnetic channel. In particular, the observed A-like and B-like phases correspond to A and B phases of bulk 3 He, regardless of presence or absence of 4 He [8][9][10][11][12][13][14]. Moreover, the superfluid transition temperature of 3 He in aerogel (T ca ) is independent on the coverage at high pressures [8,12] but slightly higher in presence of the coverage at lower pressures [15,16] probably due to the change of the scattering specularity.…”
mentioning
confidence: 85%
“…We found that ∆T ca in pure He in nafen-243 we are not able to distinguish whether the observed superfluid phase is the A phase or the DA phase because a rather large suppression of Tca does not allow us to use the rescaled bulk value of ΩA in Eq. 2 for determination of K. more strongly depends on nafen porosity than in presence of 4 He. It is especially clear for nafen-910: although its porosity is extremely low, we observed the superfluid transition for 2.5-coverage (Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations